2011
DOI: 10.1111/j.1365-294x.2011.05029.x
|View full text |Cite
|
Sign up to set email alerts
|

Stored sperm differs from ejaculated sperm by proteome alterations associated with energy metabolism in the honeybeeApis mellifera

Abstract: Sperm are exposed to substantially different environments during their life history, such as seminal fluid or the female sexual tract, but remarkably little information is currently available about whether and how much sperm composition and function alters in these different environments. Here, we used the honeybee Apis mellifera and quantified differences in the abundance and activity of sperm proteins sampled either from ejaculates or from the female’s sperm storage organ. We find that stored and ejaculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 41 publications
3
62
0
Order By: Relevance
“…Here we additionally showed that if both parameters return to male levels, females suffer infertility. While in some species, the antioxidant pathway of sperm protection has demonstrated fitness benefits for males and females2728, antioxidants only have small effects on human fertility25. It is, therefore, possible that the other fundamental pathway of oxidative stress prevention (the one confirmed here) - a suppression of the formation of oxygen radicals (and other reactive oxygen species) - is important.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Here we additionally showed that if both parameters return to male levels, females suffer infertility. While in some species, the antioxidant pathway of sperm protection has demonstrated fitness benefits for males and females2728, antioxidants only have small effects on human fertility25. It is, therefore, possible that the other fundamental pathway of oxidative stress prevention (the one confirmed here) - a suppression of the formation of oxygen radicals (and other reactive oxygen species) - is important.…”
Section: Discussionmentioning
confidence: 71%
“…consider how antioxidants capture the oxygen radicals produced by the cell782127. The effectiveness of the antioxidant pathway in improving sperm performance is currently debated252728. The second pathway concerns the extracellular (i.e.…”
mentioning
confidence: 99%
“…Thus, we hypothesize that the reduced quantity of spermatozoa recovered from the spermatheca of queens inseminated with semen from exposed drones could be also explained, independently of the phenomenon described above, by putative negative effects of such metabolic disruptions on the ability of spermatozoa to migrate. Similarly, we hypothesize that the higher mortality rate of spermatozoa observed in the spermatheca could be explained either by an impairment in the adaptation of spermatozoa having reached the spermatheca to the spermathecal fluid, which is necessary for long-term storage58, or by an increase of the mortality dynamic of the stored spermatozoa, which is a phenomenon that occurs naturally in the spermatheca over the time59.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicate that biochemical pathways linked to energy metabolism are key contributors to the specific sperm traits reported in most social insects1617. For example, proteins involved in glycolysis are significantly enriched in honeybee sperm compared with sperm of fruit flies or humans18.…”
mentioning
confidence: 99%